Perceptions towards practicability of humanitarian principles for emergency cases in Ethiopia: case of Tikur Anbessa Specialized Hospital - Habtamu Solomon Mengistu; Bezawit Negash Demissie; Gashaw Sebsibie; Biniam Bahiru (BMC, 2024)
Abstract Introduction The health of people is negatively impacted by emergencies and catastrophes, and many lives are lost as a result. The guidelines for humanitarian action during times of crisis, whether brought on by armed war or natural disasters, are provided by the humanitarian principles. The purpose of this study was to evaluate how the staff and clients at Tikur Anbessa Specialized Hospital felt about the applicability of the four humanitarian principles when responding to emergency conditions. Methodology Facility-based descriptive and explanatory cross-sectional study designs were employed. The study intended to collect data with structured questionnaires from a total of 209 individuals in Tikur Anbessa Specialized Hospital. The participants were selected randomly based on, their willingness. Of the 209 participants, 105 included staff and the rest 104 included clients (patients and caregivers in the emergency room) of Tikur Anbessa Specialized Hospital. The collected data were analyzed using Statistical Package for Social Science version 23. Results The descriptive analysis shows that principles of humanity are practiced better with (mean = 3.5) and principles of impartiality are practiced less with (mean = 3.2) as to the perception of the participants. Correlational analysis was used to examine the relationship between the ages, profession, gender, status, work experience, and familiarity with humanitarian principles, and the results indicated a non-significant correlation between variables, r (209) = 0.01 (2 tailored), "p = ns". This suggests that familiarity with humanitarian principles or other independent variables does not affect the applicability of humanitarian principles in healthcare settings. Conclusion From the results of this study, it can be concluded that the state of being a staff (health care practitioners and those providing ancillary services) and client of Tikur Anbessa Specialized Teaching Hospital has nothing to do with developing a certain perception towards the practicability of the four humanitarian principles (humanity, impartiality, neutrality, and independence).